2020
DOI: 10.1111/jam.14840
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of gas micro‐nano‐bubbles on the efficacy of commonly used antimicrobials in the food industry

Abstract: Aim To study the impact of incorporating micro‐nano‐bubbles (MNBs) in commonly used food antimicrobials (AMs) against Escherichia coli O157:H7 (EC) and Listeria monocytogenes (LM). Methods and Results Air, carbon dioxide (CO2) and nitrogen (N2) were used to incorporate MNBs in city water. AM solution (with or without MNBs) of 9 ml was individually taken into sterile test tubes and mixed with 1 ml of inoculum grown in brain heart infusion (BHI) broth to get the net AM concentrations of 28·4 ppm peracetic acid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…In a previous study, Singh et al (2020) also evaluated the effect of incorporating UFB's into the AM solutions against pure cultures of L. monocytogenes and E. coli O157:H7. The results from this study demonstrated that potency of UFB‐AM solutions does not depend on whether UFBs are incorporated before or after making AM solutions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study, Singh et al (2020) also evaluated the effect of incorporating UFB's into the AM solutions against pure cultures of L. monocytogenes and E. coli O157:H7. The results from this study demonstrated that potency of UFB‐AM solutions does not depend on whether UFBs are incorporated before or after making AM solutions.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, UFBs were generated using a micro-nano-bubble generator (LEA15; Living Energies & Co., Shizuoka, Japan) which was equipped with a pressure gauge, gas flow meter, liquid relief valve, gas relief valve, gas inlet pipe, outlet valve, and inlet and outlet hoses, as described by Singh et al (2020). The cavitation effect of introducing gas into a liquid result in production of UFB's.…”
Section: Ultrafine Bubbles Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhu et al [ 27 ] reported that nanobubbles (NBs) can prevent the fouling of surfaces and that they can also clean already-fouled surfaces. Very recently, Singh et al [ 28 ] reported CO 2 -MNBs in chlorine and peracetic acid significantly increased the potency of antimicrobial solutions against Escherichia coli O157:H7 and Listeria monocytogenes . MNBs are capable of reducing the viscosity of concentrated dispersions such as skim milk and milk protein concentrates [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Singh et al (2021), an early incorrect version of Figure 7 was published. The correct Figure 7 is reproduced below:
…”
mentioning
confidence: 99%